To study the role of tranexamic acid in the management of menorrhagia - Hangarga, U. S.; D., Rita; Reddy Edula, Reshma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Heavy menstrual bleeding is a significant case of morbidity during the reproductive years. Approximately 30% of women complain of menorrhagia and it is the main presenting problem of women consulting a gynaecologist. In addition, excessive menstrual bleeding accounts for about two-thirds of all hysterectomies. This amount of blood loss can cause disturbance of the woman’s social, occupational or sexual life, as well as medical risks such as chronic iron deficiency anemia. Objective of the study was to determine if tranexenic acid can effectively and safely reduce menstrual blood loss in menorrhagia. Methods: 100 cases selected for the study who complained of regular long/ heavy menstrual bleeding more than 7 days or blood loss more than 80ml, who are at the age of 20-45 years. This study includes measurement of menstrual blood loss, duration of bleeding, number of sanitary pad usage for two menstrual cycles who complained of regular excessive menstrual bleeding using pictogram and taken history of IUCD insertion. Abdominal, gyanecological examination and ultra sound has been done to rule out any pelvic pathology. Drug Tranexamic acid 500mg QID were given to the patients who had mean menstrual blood loss of more than 80ml based on assessment in the previous two menstrual cycles. Results: The total study shows the effect of drugs on the amount of bleeding is 41.6% (P-value <0.05), there is significant reduction is seen in number of sanitary pad usage from 5.44 to 3.96 (P- value <0.05) and there is significant reduction in duration of bleeding. There are minimal gastrointestinal side effects, and there is 32% discontinuation of treatment in our study as patient is not satisfied. Conclusions: Treatment with tranexamic acid could potentially improve quality of life of women. It is also effective treatment for menorrhagia caused by IUCD. Current clinical evidence concludes that size and type of fibroid has significant influence on effect of treatment. Tranexamic acid has been doc umented and found to have no effect on uterus with adenomyosis and endometrial polyp